Pembinaan Tahsin Al-Quran dalam Meningkat Kemampuan Membaca dan Menghafal Al-Qur’an Ayat-ayat Pilihan di MTs Roudlotul Mubtadiin - Ja’far; M.Syaikhudin (CV Putra Publisher, 2025)
This community service program was motivated by the low ability of students at MTs Roudlotul Mubtadiin to read the Quran correctly. In response to this problem, the community service team collaborated with the management of MTs Roudlotul Mubtadiin to organize a program that focuses on education, namely the Tahsin program for reading and memorizing verses of the Quran. The purpose of this community service is to improve students' ability to read the Quran according to the rules of tajwid. The results of this community service program show that the implementation of Tahsin for reading and memorizing selected verses has succeeded in improving the skills of reading the Quran and the ability to memorize holy verses in participants. As a follow-up, the Tahsin program for reading and memorizing will be included in learning activities at MTs Roudlotul Mubtadiin for students